Peranan Body Dissatisfaction dan Social Comparison dengan Kesejahteraan Psikologis Santriwati - Nuzula, Fera Firdausi; Affandi, Ghozali Rusyid (Universitas Muhammadiyah Metro, 2025)
Life in Islamic boarding schools is considered effective for achieving psychological well- being because students are active in beneficial activities. In the formation of the personality of adolescent students, understanding their psychological well-being is important, including physical changes during puberty, especially in adolescent girls.Due to hormonal influences during puberty, each adolescent experiences different physical changes. So that it often makes the psychological well-being of adolescent girls disturbed related to questioning their body shape and makingsocial comparisons. The purpose of this study was to determine the role of body dissatisfaction and social comparison on psychological well-being. The population in this research was 948 female students. The sampling technique used the Krejcie Morgan table and obtained a sample of 255 female students. Data were collected using scales of body dissatisfaction, social comparison, and psychological well-being. This research method is quantitative correlation with multiple linear regression analysis using SPSS version 29. Based on simultaneous testing (F test) of 44,457 and significance p <0.001.